Survey results of honey bee (Apis mellifera) colony losses in China (2010–2013). Issue 1 (1st January 2016) - Liu, Zhiguang; Chen, Chao; Niu, Qingsheng; Qi, Wenzhong; Yuan, Chunying; Su, Songkun; Liu, Shidong; Zhang, Yingsheng; Zhang, Xuewen; Ji, Ting; Dai, Rongguo; Zhang, Zhongyin; et al.
Abstract : Survey results of colony losses of honey bee ( Apis mellifera ) have been reported worldwide in recent years. However, there has previously been no large-scale survey reported for China, the largest beekeeping country. Here we present the result of a three-year survey from 2010 to 2013, using the standard COLOSS questionnaires. In total, we received 3, 090 responses, including 485 from part-time beekeepers, 2, 216 from sideline beekeepers, and 389 from commercial beekeepers. Colony losses were low in general (10.1%, 95% CI: 9.5–10.7%), with variations among years (ranging from 8.5 to 12.0%), provinces (ranging from 2.5 to 19.0%), and different sizes of apiaries (ranging from 7.6 to 12.1%). Generalized linear mixed effects models were used to estimate the effects of potential risk factors on colony losses. Significant factors are comb renewal, and percentage of colonies with queen problems. Random effects from the models show that variation is large at the beekeeper level, while small at the year level.